Pneumatosis coli in a domestic ferret (Mustela putorius furo) - Larouche, Cédric B. (Can Vet J, 2017)
A 4-year-old spayed female ferret was presented with acute diarrhea and partial anorexia. Pneumatosis coli and segmental enteropathy were identified by ultrasonography and radiography. Fecal culture did not identify any pathogenic bacteria. Medical management of concurrent diseases and antibiotic therapy resulted in resolution of clinical signs and pneumatosis coli.